Load distribution for an intelligent air-cushion track vehicle based on optimal power consumption - Hossain, Altab; Rahman, Mohammed Ataur; Mohiuddin, A. K. M. (Inderscience Enterprises Ltd., 2010)
This study incorporates the computation of load distribution for an intelligent air-cushion track vehicle (IACTV) based on optimal power consumption (PC). A novel design auto adjusting air-cushion system has been designed and developed to minimise the PC. Focusing on optimising total PC,three main issues were studied in this paper. First, a theoretical model is developed for optimising total PC of the vehicle and the effects of load distribution on total PC. Second, a fuzzy expert system (FES) is used to control the swamp tracked vehicle’s intelligent air cushion system and thus minimise the PC. Third, an artificial neural network (ANN) model has been developed which has been trained to predict the total PC for IACTV and to provide illustration how FES might play an important role in the prediction of PC of the vehicle’s intelligent air-cushion system.